Об одном методе определения комплексных корней дисперсионных уравнений - Бондаренко, А.А. (Видавничий дім "Академперіодика" НАН України, 2007)
The paper presents a method for the numerical solution of systems of nonlinear equations with local convergence. The method is applied to determining the complex curves of dispersional spectra for an elastic isotropic infinite layer and a waveguide with square cross-section. Data presented tabularly or graphically are in good agreement with those given in the literature.